2020
DOI: 10.3390/polym12051056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modification on the Properties of Polyetherimide and Its Carbon-Filled Composite

Abstract: The effect of oligophenylene sulfone (OPSU) and polycarbonate (PC) on the rheological, mechanical and thermal properties of polyetherimide (PEI) and a carbon-filled composite based on it was studied. It is shown that the introduction of OPSU and PC leads to a decrease in the melt viscosity of PEI and a carbon-filled composite based on it with the preservation of their mechanical properties and heat resistance at a sufficiently high level. It was found that composites with OPSU have higher mechanical and therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Solubilizers and modifiers have been used to create carbonreinforced polymer-based composites, which can improve the interfacial interactions between the material components. Commonly used modifiers and solubilizers include oligophenylene sulfone, polycarbonate, 175 a random terpolymer copolymer of styrene, acrylonitrile and glycidyl methacrylate, 176 Malay linseed oil, 177 and ionic liquid 1-Benzyl-3-methylimidazolium chloride. 178 F I G U R E 7 Summary of material, process and environmental factors influencing the quality of FDM printed parts.…”
Section: Materials Pretreatmentmentioning
confidence: 99%
“…Solubilizers and modifiers have been used to create carbonreinforced polymer-based composites, which can improve the interfacial interactions between the material components. Commonly used modifiers and solubilizers include oligophenylene sulfone, polycarbonate, 175 a random terpolymer copolymer of styrene, acrylonitrile and glycidyl methacrylate, 176 Malay linseed oil, 177 and ionic liquid 1-Benzyl-3-methylimidazolium chloride. 178 F I G U R E 7 Summary of material, process and environmental factors influencing the quality of FDM printed parts.…”
Section: Materials Pretreatmentmentioning
confidence: 99%
“…The cap shell and the mask were made of polyetherimide which has strong puncture resistance. 23,24 The surface of the mask was coated with a metal film which can reflect the radiant heat of the fire scene and block harmful rays from damaging the face and eyes. A small shawl made of basalt fiber covered with an aluminum protective layer was attached to the back of the helmet to protect the neck of the wearer.…”
Section: Carrier Design Of the Firefighter Clothingmentioning
confidence: 99%
“…Among them, nine papers relate to polymer composites reinforced with synthetic fibers. Slonov and co-workers [ 4 ] study the effect of oligophenylene sulfone and polycarbonate additions on the rheological, mechanical, and thermal properties of polyetherimide reinforced with short carbon fibers. It is revealed that the addition of oligophenylene sulfone and polycarbonate significantly reduces the melt viscosity of polyetherimide based carbon filled composites, acting as a temporary plasticizer.…”
mentioning
confidence: 99%